It Is a Catch-22 Situation! A Decade of Research Trends on Gay Wellbeing in China: A Bibliometric Analysis - Jiankun Gong; Weishan Miao (Behavioral Sciences)
The wellbeing of gay men in China is shaped by a combination of cultural, social, and political factors, yet research on this topic remains fragmented despite growing global interest in LGBTQ+ health. This study provides a comprehensive bibliometric analysis of research trends on wellbeing of gays (MSM) in China, using the PRISMA 2020 guidelines for a systematic search strategy and VOSviewer for bibliometric mapping. Data from Scopus were analyzed to examine publication output, top journals, and authors, along with a co-occurrence analysis of keywords and co-authorship networks across countries and authors. Results show a steady rise in publications over the past decade, particularly after 2015, revealing strong domestic collaboration and emerging international partnerships. The study identifies key contributing journals and themes, while revealing that most research remains narrowly focused on HIV/AIDS, leaving gaps in understanding gay wellbeing from broader societal and cultural perspectives. Surprisingly, very few studies specifically examine or measure overall wellbeing, whether using quantitative or qualitative approaches, and there is limited exploration of how cultural factors influence the experiences of gay men in China. These findings underscore the need for more holistic research approaches that move beyond public health and HIV prevention to address the psychological, social, and cultural dimensions of wellbeing.